Putative risk and resiliency factors among Royal Canadian Mounted Police cadets - Khoury, Juliana M. B.; Jamshidi, Laleh; Shields, Robyn E.; Nisbet, Jolan; Afifi, Tracie O.; Fletcher, Amber J.; Stewart, Sherry H.; Asmundson, Gordon J. G.; Sauer-Zavala, Shannon; Krätzig, Gregory P.; Carleton, R. Nicholas (Frontiers in Psychology, 2023)
Objective: Mental health disorders are prevalent among active duty Royal Canadian Mounted Police (RCMP) officers (1). The current study was designed to assess whether RCMP cadets commencing the Cadet Training Program are inherently at greater risk of developing mental health challenges by statistically comparing cadet putative risk and resiliency scores to scores from young adult populations. The study was also designed to assess for sociodemographic differences in putative risk and resiliency variables among RCMP cadets in order to facilitate future comparisons. Methods: Cadets (n = 772; 72.2% men) completed self-report measures of several putative risk variables (i.e., anxiety sensitivity, fear of negative evaluation, pain anxiety, illness and injury sensitivity, intolerance of uncertainty, and state anger) and resiliency. Scores were statistically compared to samples from Canadian, American, European, and Australian young adult populations. Results: Cadets had statistically significantly lower scores on all putative risk variables and statistically significantly higher resiliency scores compared to the young adult populations. In the cadet sample, there were statistically significant differences in putative risk and resiliency variables across gender and sex. Conclusion: Cadets’ significantly lower scores on putative risk variables and higher scores on resiliency suggest that they may be psychologically strong; as such, it may be that the nature of police work, as opposed to inherent individual differences in risk and resiliency, accounts for active duty RCMP officers’ comparatively higher prevalence of mental health disorders over time. ClinicalTrials.gov Identifier: NCT05527509